Re-conceptualizing the paradox in (education) policy implementation: unravelling perspectives on the policy/practice gap - Pius Nudzor, Hope (Hauppauge,New York: Nova Science Publishers, 2021)
'A review of current (education) policy and practice endorses the view of an apparent paradox in policy implementation. Although tremendous investments (in terms of energy, time and financial resources) are made in enacting policies, there is ample evidence to suggest that policy actors are impervious to policy information. Change agents and implementers of policy are often seen as pursuing different agendas when it comes to the task policy implementation. As aptly asserted by Sabatier and Jenkins-Smith (1993, cited by Shulock, 1999, p. 228),'policymakers and implementers' core beliefs are unaffected by policy information, major policy change results rather from external factors such as inflation and elections'. This book re-conceptualizes this policy phenomenon for rumination. The book essentially unravels perspectives on the policy implementation paradox, and through that exemplifies the'best' suited approach for demystifying the policy/practice gap to bring understanding to the messiness and contested nature of (education) policy processes. To help draw conceptual leverage on the phenomenon described as the'policy implementation paradox', this eight chapter book performs two major functions. First, Chapters 1 to 4 set the context for the book. Chapter 1 defines (education) policy, and in the process, the traditional problem-solving definition of policy is juxtaposed with the process model, and through that a third conception (i.e. the theoretical eclecticism approach) is gauged to help provide both practical and theoretical bases for understanding how policy and practice exist in dynamic and iterative relationships. Chapters 2 and 3 give insights into how education policy-making is made and implemented respectively to unravel some of the influences on policy processes. Chapter 4 explicates (from within relevant literature) the policy paradox to assist readers to understand perspectives that are advanced in latter chapters to unravel and/or explain the existence or occurrence of this policy phenomenon. Second, Chapters 5 to 7 draw on literature from disparate sources to unravel perspectives on the policy implementation paradox, whilst Chapter 8 presents the key messages that are tangential to achieving the objectives of the book. Overall, Chapter 8 performs three functions. Namely, it: summarizes perspectives presented in the scholarly literature to demystify and unravel the policy implementation paradox illustrates the reasons for the choice of the post-modernist perspective as the most appropriate and/or best suited perspective for unravelling this policy phenomenon; and outlines the relevance (and/or justifications) of the post-modernist conception of policy as both'text' and'discourse' as a framework for understanding the policy implementation paradox and the dynamism of policy processes at large'--
Defining (education) policy -- Understanding education policy-making -- Understanding the concept and nature of (education) policy implementation -- Illuminating the policy implementation paradox : using examples from education -- The change management perspective on the policy implementation paradox -- The democratic/participatory perspective on the policy implementation paradox -- The post-modernist perspective on the policy implementation paradox -- Relevance of the post-modernist perspective to understanding policy processes.
Includes bibliographical references and index.
Keywords: Education and state